Responding to ash dieback (Hymenoscyphus fraxineus) in the UK: woodland composition and replacement tree species. (5th November 2018) - Broome, A; Ray, D; Mitchell, R; Harmer, R
Abstract: Common ash ( Fraxinus excelsior L.) is an important timber species that is widespread in broadleaved woodlands across Europe, where it is currently declining due to the fungal pathogen ( Hymenoscyphus fraxineus (T. Kowal)Baral et al., 2014 ) causing ash dieback. Using the UK as our case study, we assess: (1) likely woodland composition following ash dieback and (2) choice of replacement species for production planting. The greatest impacts on woodland composition will occur where ash forms a larger proportion of the canopy. In such woodlands, larger gaps formed from the loss of ash, are likely to be filled by sycamore ( Acer pseudoplatanus L.) and beech ( Fagus sylvatica L.) under current climatic conditions and where there is little management intervention. Native woodland policy regarding sycamore and beech may need to be reviewed in UK-designated woodlands where these species are considered non-native. For actively managed production woodlands, 27 replacement tree species for ash are considered, some of these are non-native and present options for continuing production forestry objectives on former ash sites. An assessment of replacement species shows there is no single species that can substitute for the wide range of site conditions associated with the good growth of ash. In deciding to replace ash with another tree species, the decision on selection should be made based on particular site conditions and woodland objectives.